Environmental Movements in Turkey from the Perspective of Commons. Issue 1 (18th June 2021) - Hazar Kalonya, Dalya
Enclosure movements on the commons continue without slowing down especially in the developing countries; as well as the grassroots movements against them. Enclosure movements frequently contain several foreign investments and appropriations to other uses on natural resources and/or assets such as pastures, forests, rivers, agricultural lands and seashores, which are crucial income sources for rural households. Among other factors, the shortcomings in the common management processes, cooperatives and self-organization capacity of the stakeholders ease the enclosure process. The study investigates the environmental movements as commoning practices in Turkey in the last decade through media analysis and surveys. The study aims to constitute a scientific basis to enhance the EIA processes in order to encourage proactive responses to environmental crises, prevent enclosure movements on the commons and maintain the local sustainable development. Hence, firstly the environmental movements in Turkey are spatialized by GIS analyst tools to constitute an environmental inventory including time, types, frequency and location of the movements; secondly, an online survey is conducted with the environmental NGOs; thirdly, two possible scenarios are suggested through a triple-scale scoring system; and finally, several recommendations are proposed in order to sustain the commons.